Dimensional structure and course of post-traumatic stress symptomatology in World Trade Center responders. Issue 10 (2nd December 2013) - Pietrzak, R. H.; Feder, A.; Schechter, C. B.; Singh, R.; Cancelmo, L.; Bromet, E. J.; Katz, C. L.; Reissman, D. B.; Ozbay, F.; Sharma, V.; Crane, M.; Harrison, D.; et al.
Abstract : Background: Post-traumatic stress disorder (PTSD) in response to the World Trade Center (WTC) disaster of 11 September 2001 (9/11) is one of the most prevalent and persistent health conditions among both professional (e.g. police) and non-traditional (e.g. construction worker) WTC responders, even several years after 9/11. However, little is known about the dimensionality and natural course of WTC-related PTSD symptomatology in these populations. Method: Data were analysed from 10 835 WTC responders, including 4035 police and 6800 non-traditional responders who were evaluated as part of the WTC Health Program, a clinic network in the New York area established by the National Institute for Occupational Safety and Health. Confirmatory factor analyses (CFAs) were used to evaluate structural models of PTSD symptom dimensionality; and autoregressive cross-lagged (ARCL) panel regressions were used to examine the prospective interrelationships among PTSD symptom clusters at 3, 6 and 8 years after 9/11. Results: CFAs suggested that five stable symptom clusters best represent PTSD symptom dimensionality in both police and non-traditional WTC responders. This five-factor model was also invariant over time with respect to factor loadings and structural parameters, thereby demonstrating its longitudinal stability. ARCL panel regression analyses revealed that hyperarousal symptoms had a prominent role in predicting other symptom clusters of PTSD, with anxious arousal symptoms primarily driving re-experiencing symptoms, and dysphoric arousal symptoms primarily driving emotional numbing symptoms over time. Conclusions: Results of this study suggest that disaster-related PTSD symptomatology in WTC responders is best represented by five symptom dimensions. Anxious arousal symptoms, which are characterized by hypervigilance and exaggerated startle, may primarily drive re-experiencing symptoms, while dysphoric arousal symptoms, which are characterized by sleep disturbance, irritability/anger and concentration difficulties, may primarily drive emotional numbing symptoms over time. These results underscore the importance of assessment, monitoring and early intervention of hyperarousal symptoms in WTC and other disaster responders.